2020
DOI: 10.4491/eer.2020.276
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics from degradation of tires in sewer networks of the city of Riobamba, Ecuador

Abstract: Microplastics are small synthetic particles that come from petroleum derivatives, are difficult to degrade and their origin is found in industrial activity and domestic consumption, even in tires. The presence of small particles (0.1 µm to < 5 mm) of plasticizer Bis (2-ethylhexyl) phthalate (DEHP) and synthetic rubber, which due to their size and origin are called microplastics. The friction occurs between the asphalt in contact with the tires of cars generate the detachment of small residues of it, these resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…According to Sabbah et al (2019) and Freeman et al (2020), there is high variation in MPs concentration obtained per litre (0.005-91 MP particles L −1 and 0-447 MP particles L −1 ) in final effluents from different WWTPs around the world. This has led to strict regulations and standards by most environmental regulatory bodies regarding the discharge of effluent from wastewater treatment plants into the environment (Visvanathan et al 2000;Arimi 2018;Sabbah et al 2019;Cuartucci 2020;Paredes et al 2021). Thus, there is need for improving the existing technologies or the use of advance technology that is capable of removing MPs of different sizes, shapes, polymer and densities from the influent and effluent at all stages of wastewater treatment to meet the effluent discharge and reuse standards (Arimi 2018;Cuartucci 2020;and Rathilal 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to Sabbah et al (2019) and Freeman et al (2020), there is high variation in MPs concentration obtained per litre (0.005-91 MP particles L −1 and 0-447 MP particles L −1 ) in final effluents from different WWTPs around the world. This has led to strict regulations and standards by most environmental regulatory bodies regarding the discharge of effluent from wastewater treatment plants into the environment (Visvanathan et al 2000;Arimi 2018;Sabbah et al 2019;Cuartucci 2020;Paredes et al 2021). Thus, there is need for improving the existing technologies or the use of advance technology that is capable of removing MPs of different sizes, shapes, polymer and densities from the influent and effluent at all stages of wastewater treatment to meet the effluent discharge and reuse standards (Arimi 2018;Cuartucci 2020;and Rathilal 2020).…”
Section: Introductionmentioning
confidence: 99%
“…14,19,20) So far, a lot of studies reported plastic pollution in environment especially in the ocean, but mostly focused on the plastic pollution caused by secondary microplastics. 21,22) Despite of the importance of primary source, there has been a relatively lack of studies regarding the plastic pollution of primary microplastics.…”
Section: Introductionmentioning
confidence: 99%